PERAN PEMERINTAH DALAM DISTRIBUSI TANAH ATAU LAHAN PERKEBUNAN (Studi Literatur Pemikiran Ekonomi Islam Perspektif Abu ‘Ubaid Al-Qasim Bin Salam) - Irawati Irawati; Adril Hakim (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2014)
With the development and welfare reasons, the government diverts thousands hectare civil‟s gardens for the sake of oil palm plantation development. Beside the unfair handing the Ulayat land mechanism, the switch function of productive agricultural lands led to growing economic inequality which lead to the conflict. Therefore, the thought of Abu Ubaid in the book of al-Amwal regarding the law and politics in the land or plantations as a benchmark in achieving solution upon the issue. The research question in this study namely: How does the view of Abu „Ubaid about the government's role in the distribution and management of plantations? and what kind of policies is needed, so it can effectively decrease the gaps in the current farm/land owner?. The methodology in this present study used descriptive research which is library-based research. The data were analyzed qualitatively. Data used in this study is qualitative data obtained from an authentic source comprising a source of primary data and secondary data sources. The results show that that the law and the way of Abu „Ubaid provide a solution to the inequality of land ownership is very different from the government policy in Indonesia. One of the policy which is to clarify over the abandoned land by tenants is for three years and then the government takes the right for the land. The government has the authority to give the land to a new tenant who wants to turn the land becomes more productive.